KARAKTERISTIK LAMINASI BAMBU PADA PAPAN JABON - Achmad Supriadi; I.M. Sulastiningsih; Subyakto (Jurnal Penelitian Hasil Hutan, 2017)
Jabon (Anthocephalus cadamba Miq.) has been widely planted by communities as an alternative of building and furniture materials. However, there are two inferior jabon wood proferties i.e. low strength (Class IV) and less durable (Class V). Jabon-Bamboo Laminated Board (JBLB) is one posible product that may be developed to improve jabon’s wood properties. This study investigates quality improvement of jabon boards due to fabrication as JBLB and the effect of bamboo layers number on JBLB properties. Andong bamboo (Gigantochloa pseudoarundinaceae (Steudel) Widjaja) and mayan bamboo (Gigantochloa robusta Kurz) were used in this study. Initially, jabon boards and 3 bamboo strips were preserved by soaking in 7% boron solution until reaching the targeted retention of 6 kg/m . The JBLB were manufactured in four different layer compositions using Isocyanate adhesive. The glue spread and cold pressing time 2 applied were 250 g/m and one hour, respectively. Results showed that quality of JBLB was significantly affected by the number of bamboo layers, except bonding strength. Bamboo lamination on jabon board has increased the product density by 10%, modulus of elasticity (MOE) by 71%, modulus of rupture (MOR) by 34% and compression strength by 20% compared with the initial jabon properties. Strength values of JBLB are classified into wood strength class-III .